Analisis Ergonomi pada Operator Hand Tractor Menggunakan Metode Rapid Upper Limb Assesment (RULA) - Oktafian Nanda Nusila; Dwi Djumhariyanto; Digdo Listyadi Setyawan; Nasrul Ilminafik; Nur Koyim Kustanto (Jurusan Teknik Mesin, 2023)
In high technological times the use of agricultural tools with modern machinery helped accelerate the processing of agricultural production. One of the most common and most commonly used tools is the Tractor. Tractor is a motorized tool that has the ability to preparation the soil. Application of tractor to preparation the soil is mostly done by farmers. A lot of used tractors is the hand tractor. Unsuitableof factor of tractor design to operator and land condition has caused many problems related to comfort, safety and health of work. Handlebar on the hand tractor is still less comfortable and ergonomic considered by the operator. This study aims to identify hand tractor operator complaints of inconvenience in working using RULA analysis of CATIA V5R17 software. Based on anthropometry percentile calculations, the result 1100 mm handlebar height, 650 mm handlebar width, and the distance of the turning lever to a 120 mm handlebar. The percentiles used are 5, 50, and 95 presentations using CATIA V5R17.